The Influence Of Tourist Motivation And The Quality Of Special Interest Tourism On Tourist Satisfaction For Live-In Tour Packages In Lerep Tourist Village - Natasya Grecoria Jaro Br Ginting; Trenggono Trenggono; Nilamtoro Ayungga Dewi; Nogiya Cindy Andani (International Conference On Digital Advanced Tourism Management And Technology, 2023)
The purpose of this research is to explain the influence of tourist motivation and the quality of special interest tourism on tourist satisfaction in live-in tour packages in Lerep tourist village. This research uses quantitative methods. The population in this study were live-in tourists in the Lerep Tourism Village whose population was known to be 240 tourists from January – June 2023, then calculated using the Slovin formula result in 70 respondents are needed as research samples. The sampling technique is accidental sampling. The results show that Tourist Motivation and the Quality of Special Interest Tourism partially and simultaneously have a significant effect on Tourist Satisfaction for Live-in tour Packages in Lerep Tourism Village, where the Quality of Special Interest Tourism is the dominant factor for tourists in increasing Tourist Satisfaction, compared to Tourist Motivation. From the results of calculating the coefficient of determination, the two independent variables contributed high influence of 60.2%.